Strange teaching activity: a marxian analysis of the situation of education professionals (Research, Society and Development, 2020)
This article aims to analyze teaching activity in the light of the strangeness category. To this end, the pertinent literature on issues related to work, alienation and estrangement was revisited using Lukács, Marx, Antunes, Antunes & Pinto, and Lessa; and as theoretical references on the issue of education and teaching activity in Brazil, Arroyo and Apple were used. As for the methodology, it is a theoretical research, in the dialectic historical materialist perspective that tries to search for signs of strange work in the teaching activity of Basic Education professionals in Brazil. It can be inferred, therefore, that the teaching profession suffers interference from the capitalist market regime, thus the activity developed daily by salaried teachers can also be considered as an activity with aspects of alienation and / or estrangement.